2018
DOI: 10.1089/jwh.2017.6465
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Health Insurance Coverage of Title X Family Planning Program Clients, 2005–2015

Abstract: Although clients attending Title X clinics remained uninsured at substantially higher rates compared with the national average, the increase in clients with health insurance coverage aligns with the implementation of ACA-related provisions to expand access to affordable health insurance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Research using clinic-level data has demonstrated that Title X clinics provide better access to LARC methods than non–Title X clinics . Historically, Title X has been the most important payer for contraceptive services for women with low incomes, and the exit of Planned Parenthood and individual states from the Title X program may intensify the role of non–Title X CHCs as publicly funded contraceptive care providers…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research using clinic-level data has demonstrated that Title X clinics provide better access to LARC methods than non–Title X clinics . Historically, Title X has been the most important payer for contraceptive services for women with low incomes, and the exit of Planned Parenthood and individual states from the Title X program may intensify the role of non–Title X CHCs as publicly funded contraceptive care providers…”
Section: Discussionmentioning
confidence: 99%
“…We identified patients who visited a Title X clinic within the measurement year because Title X clinics are known to provide broader range of contraceptive methods, including LARC . Title X funding status of the clinic was determined from data from the OPA .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies (n = 53) examined the impact of the ACA (signed into law in 2010) on contraceptive access, finding that the ACA decreased rates of uninsurance among American women (Decker et al, 2018;E. M. Johnston & McMorrow, 2020;Jones & Sonfield, 2016;Kavanaugh et al, 2018;MacCallum-Bridges & Margerison, 2020;Riddell et al, 2018;Willage, 2019) and increased the proportion of patients paying for services with insurance (Arora & Desai, 2016).…”
Section: Affordable Care Actmentioning
confidence: 99%
“…In states that did not adopt the expansion, Medicaid coverage increased far less, from 23% to 26%. 7 However, this descriptive study did not isolate the causal impact of Medicaid expansion and it did not consider the effects of expansion on other outcomes such as client volumes or the mix of services provided. An analogous body of research has examined the effect of expansion on other types of safety-net clinics.…”
Section: Introductionmentioning
confidence: 99%